2017
DOI: 10.4172/2090-7214.1000268
|View full text |Cite
|
Sign up to set email alerts
|

Does Labor Augmentation with Oxytocin Increase the Risk of Postpartum Hemorrhage? A Randomized Controlled Trial

Abstract: Labour augmentation aims to shorten labour so prevent complications related to prolonged labour. There is evidence that a significant proportion of women with uncomplicated pregnancies are subjected to routine augmentation of labour with oxytocin in spite of the general rule that labour augmentation should only be performed for valid indications. Obstetric hemorrhage is one of the leading causes of maternal mortality in developing countries, accounting for 10%-30% of direct maternal deaths. The aim of the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Not surprisingly, the strongest risk factor in our study is requiring manual removal of placenta due to retained placental tissue, which is universally known as the second-leading cause of PPH [34,51]. Augmentation of labor was also supported by many previous observational studies [52,53], as well as being consistent with one randomized control trial, which found that labor augmentation increases the volume of postpartum blood loss [54]. The hypothesized mechanism was the reduction in the uterine contractility after birth due to desensitized oxytocin receptors at the uterus [55].…”
Section: Discussionsupporting
confidence: 87%
“…Not surprisingly, the strongest risk factor in our study is requiring manual removal of placenta due to retained placental tissue, which is universally known as the second-leading cause of PPH [34,51]. Augmentation of labor was also supported by many previous observational studies [52,53], as well as being consistent with one randomized control trial, which found that labor augmentation increases the volume of postpartum blood loss [54]. The hypothesized mechanism was the reduction in the uterine contractility after birth due to desensitized oxytocin receptors at the uterus [55].…”
Section: Discussionsupporting
confidence: 87%
“…The Lagos pilot study also highlighted lack of guidelines and has helped inform the ongoing advocacy for the relevant stakeholders to address this concern. Currently, most guidelines used in Nigeria are based on experiences and recommendations from the United States, Canada, and the United Kingdom, which have recommended a low dose of oxytocin (2.5IU up to 5IU) intrapartum, with much more caution when being used in multiparous women [ 38 ]. For the prevention of PPH, most guidelines and clinical practice recommend 10IU intramuscular or intravenous [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oxytocin when used for labour induction/augmentation can cause both maternal and foetal adverse outcomes [ 2 , 10 ], hence the need for strict adherence to recommendations and adequate provision for close monitoring [ 4 , 7 ]. Oxytocin used during labour has been associated with increased risks of neonatal encephalopathy [ 11 ], and increases the volume of blood loss during vaginal birth [ 12 ]. A Cochrane systematic review has shown that oxytocin used during labour has poor efficacy in reducing rates of caesarean section, and instrumental deliveries and is associated with uterine hyperstimulation and foetal heart rate changes [ 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%